Higher Hemoglobin A1c Level Is Associated With Poor Outcome of Intracerebral Hemorrhage - Liu, Huihui; Meng, Xia; Liu, Chun-Feng; Wang, David; Zheng, Huaguang; Li, Hao; Liu, Liping; Wang, Yilong; Wang, Yongjun; Pan, Yuesong (Frontiers in Neurology, 2019)
Background: Pre-morbid chronic hyperglycemia is associated with the poor outcome of ischemic stroke, but the association between chronic hyperglycemia and the long-term outcome of acute intracerebral hemorrhage is still poor understood. Methods: Data on patients with acute intracerebral hemorrhage in the ACROSS-China registry (Abnormal Glucose Regulation in Patients With Acute Stroke Across China) were reviewed. Elevated hemoglobin A1c (HbA1c) level on admission was indicative of chronic hyperglycemia. According to the clinical categories of HbA1c, patients were divided into three groups. Multivariable logistic regression or Cox method was performed to analyze the association of HbA1c and the prognosis of patients with acute intracerebral hemorrhage (poor functional outcome [modified Rankin scale score 3–6] and mortality) at 1 year. Results: A total of 416 patients were included in this study. Fifty two (12.5%) patients died and 130 (31.8%) had poor functional outcome at 1-year follow-up. The higher levels of HbA1c (≥ 6.5%) was associated with a poor functional outcome (OR 2.35, 95% CI, 1.28-4.29) and increased mortality (OR 2.63, 95% CI 1.34-5.15), compared with the lowest category. When further stratified by diabetic or nondiabetic medical history, higher HbA1c (≥ 6.5%) still increased the risk of poor functional outcome (OR 3.42, 95% CI 1.39-8.44) and mortality (OR 4.48, 95% CI 1.64-12.24) in patients with non-diabetic medical history. However, higher HbA1c didn’t have the association with the increased risk of poor functional outcome (OR1.06, 95% CI 0.37-3.03) and mortality (OR 1.20, 95% CI 0.39-3.72) in patients with diabetic medical history. Conclusions: Higher HbA1c was associated with higher risk of death and poor functional outcome one year after intracerebral hemorrhage, especially in patients without a diabetic history.